Outcomes of Visual Self-Expression in Virtual Reality on Psychosocial Well-Being With the Inclusion of a Fragrance Stimulus: A Pilot Mixed-Methods Study - Kaimal, Girija; Carroll-Haskins, Katrina; Ramakrishnan, Arun; Magsamen, Susan; Arslanbek, Asli; Herres, Joanna (Frontiers in Psychology, 2020)
Aims: In this pilot mixed methods study, we examined participant experiences of engaging in virtual drawing tasks and the impact of an olfactory stimulus (calming fragrance blend) on outcomes of affect, stress, self-efficacy, anxiety, creative agency, and well-being (satisfaction with life). Methods: This study used a parallel mixed methods, simple block randomization design. Study participants included 24 healthy adults aged 18 to 54 years, including 18 women and 6 men. Participants completed two 1-hour immersive virtual artmaking sessions and were randomly assigned to receive either a fragrance or non-fragrance condition for the first session. Quantitative (standardized self-report measures) and qualitative (open-ended survey responses and virtual artwork) datasets were collected concurrently and integrated during data analysis. Results: Quantitative results indicated that the fragrance condition demonstrated significant reduction in negative affect (e.g., feelings hostile, jittery, upset, distressed etc.), namely, reduced feelings of negativity when compared to the non-fragrance condition. A trend towards improvement in self-efficacy was also seen in the fragrance condition. No significant changes were found for fragrance or non-fragrance conditions for positive affect, anxiety, and creative agency. Qualitative findings included 5 themes related to artmaking experiences in virtual reality in both conditions: fun and joy; novelty of virtual media, experimentation, and play; relaxation and calm; learning curve; physical discomfort and disorientation. Four themes were identified for virtual art content and visual qualities: nature imagery; references to memories and personal symbols; fantasy and play within imagery; depiction of everyday objects. Conclusions: Overall, participants reported positive responses to the novel virtual artmaking experiences which were further heightened by the inclusion of the fragrance stimulus for negative affect. These preliminary findings need to be replicated with larger sample sizes to confirm the outcomes and trends that were seen in this pilot study. Further research is recommended to examine the differences between experiences of virtual and traditional art media, and to examine different olfactory stimuli promoting focus and concentration.